Umbilical Cord-Derived Mesenchymal Stem Cells Suppress Autophagy of T Cells in Patients with Systemic Lupus Erythematosus via Transfer of Mitochondria - Jinyun Chen; Qian Wang; Xuebing Feng; Zhuoya Zhang; Linyu Geng; Ting Xu; Dandan Wang; Lingyun Sun (Hindawi Limited, 2016)
Aberrant autophagy played an important role in the pathogenesis of autoimmune diseases, especially in systemic lupus erythematosus (SLE). In this study, we showed that T cells from SLE patients had higher autophagic activity than that from healthy controls. A correlation between autophagic activity and apoptotic rate was observed in activated T cells. Moreover, activation of autophagy with rapamycin increased T cell apoptosis, whereas inhibition of autophagy with 3-MA decreased T cell apoptosis. Umbilical cord-derived mesenchymal stem cells (UC-MSCs) could inhibit respiratory mitochondrial biogenesis in activated T cells to downregulate autophagy and consequently decrease T cell apoptosis through mitochondrial transfer and thus may play an important role in SLE treatment.